Depression and ischemic heart disease. (1st October 2022) - Pivato, Carlo A.; Chandiramani, Rishi; Petrovic, Marija; Nicolas, Johny; Spirito, Alessandro; Cao, Davide; Mehran, Roxana
Abstract: Depression is common in patients with ischemic heart disease, and depressed patients are more likely to develop atherosclerosis and experience major cardiac events compared with the general population. The underlying pathophysiological mechanisms of these two diseases are highly interwoven and include an increased release of stress hormones, dysregulation of the autonomic nervous system, alterations of pathways related to primary and secondary hemostasis, endothelial dysfunction, and higher level of residual inflammation. Furthermore, depression negatively impacts compliance with medication regimens. As such, early recognition and treatment of depression provide the opportunity to improve outcomes of patients with ischemic heart disease. In the present review, we provide a summary of the evidence on the epidemiology, pathophysiology and management of depression in patients with ischemic heart disease. Highlights: Ischemic heart disease (IHD) and depression are leading causes of disability worldwide. Depression is more common in patients with IHD than in the general population. Depressed patients with IHD are at increased risk of adverse cardiovascular events. Early recognition of depression is pivotal in the management of patients with IHD.